Agustín Sánchez Vidal, Buñuel, Lorca, Dalí: el enigma sin fin. Planeta, Barcelona, 1988; 380 pp. - Fernández Cifuentes, Luis (El Colegio de México, 1989)
Se reseñó el libro: Buñuel, Lorca, Dalí: el enigma sin fin.